The Drosophila G protein-coupled receptor, GulpR, is essential for lipid mobilization in response to nutrient-limitation - Barraza, Daniela; Ding, Xiang; Findley, Lauren; Wang, Zihuan; Jugder, Bat-Erdene; Watnick, Paula I. (PLOS Genetics, 2025)
Author summary Humans and other animals, including Drosophila, catabolize dietary nutrients such as polysaccharides, lipids, and proteins into simple sugars, fatty acids, and amino acids, respectively, to generate the energy that fuels essential cellular processes like cell division, ion transport, muscle contraction, and more. The ability to adapt to changes in nutrient availability and energy demand is therefore crucial for homeostasis and survival. Nutrient scarcity and the energy demands of an immune response against pathogenic infection require utilization of the body’s own lipid and glycogen stores. This adaptive response largely relies on the ability of the intestine to sense and respond to a variety of stimuli, including microbes and dietary nutrients. Here, we have characterized a Drosophila melanogaster receptor that is expressed in a rare intestinal cell type with endocrine function. We report that this receptor regulates production of peptide hormones that are known to impact metabolic homeostasis and discover that one of these peptide hormones is crucial for utilization of systemic lipid stores under nutrient limitation but not infection stress. Our findings therefore indicate that lipid mobilization in response to nutrient limitation and infection are regulated via different mechanisms.